What Motivates to Transfer of Training? Empirical Analysis of Selected Training Institutions. (Bangladesh Journal of Public Administration, 2022)
Training organizations in the public sector, on the other hand, have a mission to arrange training programs for human resource development at all levels. As a result, the training program's goal is to increase trainees' capacity in terms of skill, knowledge, and work behavior (attitude) so that they can offer better service to citizens.The Bangladesh Public Administration Training Centre (BPATC) and Bangladesh Public Service Administration Academy (BCSAA) are responsible for providing civil officials with training. The government has made training and development the highest priority, investing much in this domain. Motivation to the transfer of training has many folds; therefore, this study aims to identify the factors for motivation to transfer of training and find out the relationship of influencing factors for motivation to training transfer.The research took a quantitative method. The respondents have worked in the field and have received training from either BPATC or BCSAA or both training organizations. Using standardized questionnaire item scores ranging from "strongly agree" to "strongly disagree," data was collected from respondents.This study employed a purposeful random sampling approach. Because of the COVID-19 pandemic, an online questionnaire (emailing) was circulated to 1800 participants who had received training from BPATC and BCSAA. A total of 307 respondents participated in the study.A model was developed based on research hypotheses. Model and formulated hypotheses were tested by Regression and Coefficient results, some hypotheses are shown positive and significant impact on the transfer of training. The regression model is significant, according to the results. Furthermore, some factors have a positive effect on motivation to transfer training according to Standardize coefficient value and level of significance (p